Simple HAWT Prototype Efficiency at Small Scale Wind Speed - Melda Latif; Mumuh Muharam; Yonggi Puriza; Gusriwandi Gusriwandi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Nowadays, the wind energy research for alternatif anergy has been progress. Wind energy can be found if the wind turbine is available. Based on rotation axis, wind turbin has been classified to Horizontal Axis Wind Turbine (HAWT) and Vertical Axis Wind Turbine (VAWT). This paper explains  simple HAWT prototype to 200 ohm resistor and LED at small scale wind speed. The blade material is acrilic. This material property is light, no easy broken, no corrosive and easy to find it. The blade model is flat plate section. Rotor diameter is 1 meter. The research was did at the beach. Permanent magnet synchronous generator is used to change wind energy to electric energy. The result shows that the generator increase linearly with wind speed. Measured wind speed was 1.9 m/s to 3.9 m/s. Average efficiency of HAWT prototype was 6.2% at delta connected load and 3.7% at wye connected load.